2022
DOI: 10.1039/d2cy00864e
|View full text |Cite
|
Sign up to set email alerts
|

Primary amines from lignocellulose by direct amination of alcohol intermediates, catalyzed by RANEY® Ni

Abstract: Primary amines are crucially important building blocks for the synthesis of a wide range of industrially relevant products. Our comprehensive catalytic strategy presented here allows to source diverse primary amines...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Wu et al demonstrated the potential of this hydrogen-borrowing strategy for the conversion of lignin-derived monomers directly after the reductive catalytic fractionation of lignocellulosic biomass. 176 They applied a RANEY® Ni catalyst and obtained high conversions (>90%) for dihydroconiferyl alcohol (model compound) and 4.6 wt% yield for an actual bio-oil rich in this model compound. Thus, it can be concluded that amination via hydrogen-borrowing is a promising method when starting with lignin-derived monomers obtained via fractionation or depolymerization instead of a lignin feedstock.…”
Section: Green Methods To Adjust the Types Of Oh Groups In Lignin And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al demonstrated the potential of this hydrogen-borrowing strategy for the conversion of lignin-derived monomers directly after the reductive catalytic fractionation of lignocellulosic biomass. 176 They applied a RANEY® Ni catalyst and obtained high conversions (>90%) for dihydroconiferyl alcohol (model compound) and 4.6 wt% yield for an actual bio-oil rich in this model compound. Thus, it can be concluded that amination via hydrogen-borrowing is a promising method when starting with lignin-derived monomers obtained via fractionation or depolymerization instead of a lignin feedstock.…”
Section: Green Methods To Adjust the Types Of Oh Groups In Lignin And...mentioning
confidence: 99%
“…In this approach, hydrogen is liberated upon the direct catalytic dehydrogenation of an alcohol to a more electrophilic carbonyl, followed by in situ condensation with an amine and consecutive imine-to-amine reduction, whereby the hydrogen is consumed. [174][175][176] High selectivity and high atom economy, with water as the only byproduct, are the main advantages of amination via hydrogen borrowing. Furthermore, no external hydrogen source is needed given that this strategy is based on a hydrogen borrowing mechanism.…”
Section: Green Aminationmentioning
confidence: 99%
“…, high temperature, high catalyst loading, long reaction time) compared to similar amination of less complex aliphatic alcohols . Preferential coordination of the phenolic group to the catalyst surface and catalyst deactivation have been proposed as possible causes, but dedicated studies on this issue are still lacking in the literature. , …”
Section: Introductionmentioning
confidence: 99%
“…In order to transform alcohols into amines, hydrogen borrowing (HB) has proven itself as an atom-efficient and straightforward methodology. 11−14 Lignin-derived monomers dihydroconiferyl alcohol (1G) and dihydrosinapyl alcohol (1S) have successfully been aminated with NH 3 15 and various secondary amines 16,17 using both homogeneous (Ru) and heterogeneous (Ni, Cu) catalysts following this HB strategy. The mechanism involves initial alcohol dehydrogenation to a carbonyl intermediate, subsequent in situ condensation with the amine reactant, and final hydrogenation to the amine product, as illustrated in Scheme 1 for dimethylamine (DMAn).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation